[Poly Royal Queen Pat Base and Princesses Patti Kaser and Rheua Nell Chase with Cal Poly Aeronautics student standing] (1956)
1956 Poly Royal Queen and princesses (l to r): Princess Patti Kaser, Queen Pat Base, and Princess Rheua Nell Chase, sitting on the wing of a skystreak jet research aircraft.